Analysis of Learning Difficulties in Reading Al-Qur'an in Adolescent Students at The Khodijah Tahfizh House, Pondok Aren South Tangerang - Rahman, Ariq Fadillah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explain and describe the difficulties of adolescent students in overcoming learning difficulties in reading the Qur'an at Khadijah Tahfizh House. This research uses a qualitative method with a descriptive type. Data collection techniques used observation, interviews, and documentation techniques. The data analysis stage includes limiting research studies by reducing data, displaying and verifying data. Test the validity of the data using the necessary observation and triangulation. The subjects of this research are Tahsin subject teachers and teenage students of Khadijah Tahfizh House. The results of the research on the difficulties of adolescent students in reading the Qur'an, among others: (1) teenage students have difficulty in distinguishing letters, (2) errors in makhroj (the place where letters come out) and properties (properties that accompany each letter), (3) mad duration errors (short length of letters), (4) errors in ghunnah (holding or buzzing letters). Among the influencing factors are: (1) not associating with competitive friends, (2) lack of support and cooperation from parents when studying at home. The implication of difficulties in learning to read the Qur'an is that teachers at tahfidz institutions can serve as references in the learning process. As for solutions for tahfidz institutions, they can develop programs when accepting new students, teaching methods, and evaluate them regularly.